Handling of Nusyuz Cases in Marriage According to the Aceh Family Law Qanun (Ahwal Al-Syakhsiyah) Number 2 Of 2019 - Zaki Satria (Rechtsvinding, 2025)
This study aims to analyze the handling of nusyuz cases in marriage according to the Aceh Family Law Qanun (Ahwal Al-Syakhsiyah) Number 2 of 2019 and its implications for the protection of the rights and obligations of spouses. Nusyuz is understood as the disobedience of one party toward marital obligations, which has the potential to cause disharmony within the household. This research employs a normative juridical approach, using statutory analysis of Aceh Qanun Number 2 of 2019, supported by secondary legal materials in the form of classical Islamic jurisprudence and contemporary Islamic family law literature. The findings indicate that the Qanun regulates nusyuz comprehensively by emphasizing principles of justice, deliberation, and reconciliation prior to pursuing further legal measures. The handling of nusyuz is not solely oriented toward the imposition of sanctions but is directed toward the restoration of marital relations through advice, mediation, and the involvement of the Sharia Court. Furthermore, the Qanun seeks to balance Islamic legal values with human rights principles, particularly in preventing domestic violence and discrimination within marriage. Nevertheless, the implementation of nusyuz provisions continues to face challenges, including differing interpretations among law enforcement officials and the community, as well as limitations in supervision mechanisms. This study is expected to contribute academically to the development of Islamic family law in Aceh and to serve as a reference for policymakers and Sharia judicial practitioners in handling nusyuz cases in a fair and proportional manner. Accordingly, this research underscores the importance of harmonizing Acehnese local norms, national law, and Islamic values in building a responsive family law system oriented toward public welfare and substantive justice for Muslim families.